1988
DOI: 10.1152/ajpendo.1988.255.5.e660
|View full text |Cite
|
Sign up to set email alerts
|

PTH elevates inositol polyphosphates and diacylglycerol in a rat osteoblast-like cell line

Abstract: Parathyroid hormone (PTH)-stimulated signal transduction through mechanisms alternate to adenosine 3',5'-cyclic monophosphate (cAMP) production were studied in UMR 106-01 cells, a cell line with an osteoblastic phenotype. PTH produced transient, dose-related increases in cytosolic calcium [( Ca2+]i), inositol trisphosphates, and diacylglycerol (DAG). Both inositol 1,4,5-trisphosphate (Ins-1,4,5P3) and inositol 1,3,4-trisphosphate (Ins-1,3,4P3) production were rapidly stimulated by PTH. Consistent with the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 30 publications
6
64
1
Order By: Relevance
“…There is a general consensus that the hormone stimulates cAMP formation, but in addition, several laboratories reported activation of P! turnover, PKC or calcium mobilization [1,[19][20][21][22][23]. The latter signal has been proposed to arise independently of the formation of IP 3 [24], and studies carried out in our hands are in agreement with this notion (K. Seuwen and H. Boddeke, manuscript in preparation).…”
Section: Discussionsupporting
confidence: 80%
“…There is a general consensus that the hormone stimulates cAMP formation, but in addition, several laboratories reported activation of P! turnover, PKC or calcium mobilization [1,[19][20][21][22][23]. The latter signal has been proposed to arise independently of the formation of IP 3 [24], and studies carried out in our hands are in agreement with this notion (K. Seuwen and H. Boddeke, manuscript in preparation).…”
Section: Discussionsupporting
confidence: 80%
“…In bone, the PTH receptor (PTH1R), a seven-transmembrane domain receptor coupled to G-proteins, is highly expressed in osteoblasts and osteocytes (13). Binding of PTH to its receptor immediately activates two well defined signal transduction pathways in osteoblasts: the PKA pathway (14) in which G␣ s stimulates production of cAMP and activation of PKA, and PKC pathway (15) in which G␣ q activates phospholipase C␤ with subsequent formation of diacylglycerol and 1,4,5-inositol trisphosphate and PKC activation. We and others (16) have demonstrated that PKA pathway is the major route responsible for the anabolic action of PTH on bone in rodents.…”
Section: Pth1-34 or Wnt Agonist As Possible Therapy For Radiation-indmentioning
confidence: 99%
“…3A). PTH signals through both PKA and PKC pathways after binding with its receptor, PTH1R, on the osteoblast membrane (22,23). To study which pathway PTH uses to regulate MCP-1, we took advantage of different peptide fragments of PTH that activate different pathways as well as inhibitors and activators of these pathways.…”
Section: Pth Stimulation Of Mcp-1 Is Dose-dependent Via the Pka Pathwmentioning
confidence: 99%